Assessment and diagnosis of insomnia for clinical and research practice: a scoping review protocol (Research, Society and Development, 2021)
Insomnia is one of the leading sleep disorders, affecting different age groups, influencing individual’s ability to perform daily life activities, and ultimately diminishing their quality of life. This scoping review aims to identify instruments applied for the diagnosis of insomnia in clinical and research settings to support the nursing process and the decision-making. This review is based on the scope review framework proposed by Peters et al. (2020). The research strategy outlined aims to find studies published in the CINAHL (EBSCOhost) electronic database, Scopus, PubMed and WoS Portals. Grey literature will be accessed through free search via Google and Google Scholar, CAPES Thesis Repository, the Organizations Sleep Brazilian Association and World Sleep Society. This scope review is expected to assist nurses in the clinical reasoning process for identifying Nursing Diagnosis “insomnia”. In addition to the contribution to the research area, a proposal to include an insomnia assessment instrument(s) as diagnostic indicators in the NANDA-I taxonomy is planned. It should be noted the low volume of publications of scope review protocols. This protocol has been registered with the Open Science Framework under DOI 10.17605/OSF.IO/8MRPG.